2004
DOI: 10.1152/ajpheart.01145.2003
|View full text |Cite
|
Sign up to set email alerts
|

Upregulation of endothelial nitric oxide synthase in rat aorta after ingestion of fish oil-rich diet

Abstract: López, Diego, Xavier Orta, Kelly Casós, M. Puy Sáiz, Pere Puig-Parellada, Mireia Farriol, and M. Teresa Mitjavila. Upregulation of endothelial nitric oxide synthase in rat aorta after ingestion of fish oil-rich diet. Am J Physiol Heart Circ Physiol 287: H567-H572, 2004. First published April 1, 2004; 10.1152/ajpheart.01145.2003.-A previous study with aortic segments isolated from rats fed a fish oil-rich diet indicated an increase in acetylcholine-induced nitric oxide ( ⅐ NO)-mediated relaxation. However, it … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
34
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(37 citation statements)
references
References 42 publications
3
34
0
Order By: Relevance
“…Also eNOS protein expression increased following treatment. These data show an activation of pro NO-synthetic pathways in the aorta mediated by n-3 PUFA in accordance with previous reports [47]. However, these results, in an experimental menopause setting, do not cause an effective impact on endothelial function or total NO synthesis in the aorta, as shown both by ex vivo functional inhibition experiments and by isolated enzyme activity assays.…”
Section: Discussionsupporting
confidence: 92%
“…Also eNOS protein expression increased following treatment. These data show an activation of pro NO-synthetic pathways in the aorta mediated by n-3 PUFA in accordance with previous reports [47]. However, these results, in an experimental menopause setting, do not cause an effective impact on endothelial function or total NO synthesis in the aorta, as shown both by ex vivo functional inhibition experiments and by isolated enzyme activity assays.…”
Section: Discussionsupporting
confidence: 92%
“…Previous reports showed that ω-3FAs activated the endothelial NO synthatase, which led to increase NO production. [11][12][13] Another report showed that all polyunsaturated fatty acids reduced the inducible NOS and nitrite accumulation in vitro. [23] The wide variation in serum levels of NO and peroxynitrite could be related to the dual effects induced by ω-3FAs on nitric oxide synthatase enzymes.…”
Section: Discussionmentioning
confidence: 99%
“…[10] The beneficial effect of ω-3FAs on endothelial function is mediated by increasing the activity of endothelial nitric oxide (NO) synthatase and thereby NO production. [11,12] Six week supplementation of EPA and DHA produced significant increase in serum NO level at rest and after a judotraining session. [13] In vitro using retinal microvascular endothelial cells, DHA improved NO bioavailability and decreased superoxide anion (Ö) production.…”
mentioning
confidence: 99%
“…The fluorescence intensities were corrected by subtracting the non-specific fluorescence in wells without addition of DAF-2 DA and in wells without cells. The endothelial NO production in aortas was measured by electron spin resonance (ESR) as described previously (29). Results are expressed as relative intensity units per milligram of tissue.…”
Section: Measurement Of No Productionmentioning
confidence: 99%